2021
DOI: 10.3390/healthcare9091177
|View full text |Cite
|
Sign up to set email alerts
|

Older Seniors during the COVID-19 Pandemic—Social Support and Oral Health-Related Quality of Life

Abstract: The coronavirus disease (COVID-19) has greatly affected all parts of private life and led to social distancing and self-isolation. Limited social support for older or frail people might have led to decreased oral health and its related quality of life. The current study aimed to investigate the social support of older seniors and self-perceived oral health-related quality of life (OHRQoL) over the course of the COVID-19 pandemic. Questionnaires were sent to all patients of the Dental Clinic of the University o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…This, coupled with boredom and the monotony of daily life, led to feelings of loneliness [24,31,34]. Some of the participants spoke about the fact that many older adults feel depressed, neglected or demotivated [9,22,67], leading to problems in self-care: forgetting to take medication, malnutrition and safety issues [68,69]. The majority emphasize that the somatision is a direct consequence of feeling neglected and lonely [70].…”
Section: Discussionmentioning
confidence: 99%
“…This, coupled with boredom and the monotony of daily life, led to feelings of loneliness [24,31,34]. Some of the participants spoke about the fact that many older adults feel depressed, neglected or demotivated [9,22,67], leading to problems in self-care: forgetting to take medication, malnutrition and safety issues [68,69]. The majority emphasize that the somatision is a direct consequence of feeling neglected and lonely [70].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between SES and self-reported oral health status was partially mediated by social support with an effect size of 12% and the SES indirect mediating effect via social support was 0.03, signified that social support had a positive mediating effect between SES and self-reported oral health status and in this model, the correlation coefficient was 0.03. Previous studies had already found that the social support was positively associated with oral health [ 27 , 64 ], indicating the higher level of social support, the more likely to have good self-reported oral health status. A study had shown that SES could promote the health status by increasing social support among Chinese older adults [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed social support played an important role in improving oral health outcomes for immigrants [24][25][26]. A larger number of studies had shown that individuals with lower levels of social support often had poorer oral health [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…In the elderly prone to periodontal complications, interruption of home life and dental care due to COVID-19 may exacerbate periodontal disease [19]. Weber et al [20] reported that the decrease in dental-related quality of life of older adults requiring care during the COVID-19 pandemic was significantly associated with decreased social support. Further studies are needed to determine the impact of necessary social support during the spread of COVID-19 infection on dental visits in Japan.…”
Section: Discussionmentioning
confidence: 99%